2016
DOI: 10.1007/s00251-016-0964-4
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism at expressed DQ and DR loci in five common equine MHC haplotypes

Abstract: The polymorphism of Major Histocompatibility Complex (MHC) class II DQ and DR genes in five common Equine Leukocyte Antigen (ELA) haplotypes was determined through sequencing of mRNA transcripts isolated from lymphocytes of eight ELA homozygous horses. Ten expressed MHC class II genes were detected in horses of the ELA-A3 haplotype carried by the donor horses of the equine Bacterial Artificial Chromosome (BAC) library and the reference genome sequence: four DR genes and six DQ genes. The other four ELA haploty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…For this reason, MHC microsatellite markers are commonly used for diversity studies not only in horses but also in sheep, platypus, cats, giant pandas, rodents, and even in fish . They allow assessing the extent of polymorphism not only for single loci but they also can be helpful for defining haplotypes . Genetic diversity of complex regions such as MHC or NKR can be inferred based on strong linkage disequilibrium observed in these regions in various species (reviewed by 11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, MHC microsatellite markers are commonly used for diversity studies not only in horses but also in sheep, platypus, cats, giant pandas, rodents, and even in fish . They allow assessing the extent of polymorphism not only for single loci but they also can be helpful for defining haplotypes . Genetic diversity of complex regions such as MHC or NKR can be inferred based on strong linkage disequilibrium observed in these regions in various species (reviewed by 11).…”
Section: Discussionmentioning
confidence: 99%
“…36,37 They allow assessing the extent of polymorphism not only for single loci but they also can be helpful for defining haplotypes. 24,38 Genetic diversity of complex regions such as MHC or NKR can be inferred based on strong linkage disequilibrium observed in these regions in various species (reviewed by 11). Several studies have showed that genetic diversity assessed by MHC-linked microsatellites correlated with data based on polymorphism of MHC genes.…”
Section: Panel Of Markers Selected For Evaluation Of Mhc Diversity Inmentioning
confidence: 99%
“…The horse's MHC includes several gene families with polymorphic loci that vary extensively in nucleotide diversity and in copy number of paralogous genes. Some of its molecular structure could recently be characterized, including several MHC class I (Tallmadge, Campbell, Miller, & Antczak, ) and MHC class II genes (Miller et al., ; Viļuma et al., ) of the Thoroughbred, Standardbred and the Arabian breeds. However, many MHC genes of other breeds are not sufficiently characterized at the molecular level, including several MHC genes of the Franches‐Montagnes breed we use here.…”
Section: Methodsmentioning
confidence: 99%
“…As in previous studies on horses [7][8][9][10] , a pair was classified as "MHC similar" if at least one ELA was shared between a stimulus stallion and a mare, and as "MHC dissimilar" if no ELA were shared. We decided against genotyping by MHC-linked microsatellites 54 because microsatellites are more likely to over-estimate variation in MHC structural genes than serological methods 55 .…”
Section: Mhc Determinationmentioning
confidence: 99%